2022
DOI: 10.3390/ijerph191610350
|View full text |Cite
|
Sign up to set email alerts
|

Exercise to Improve Postural Stability in Older Adults with Alzheimer’s Disease: A Systematic Review of Randomized Control Trials

Abstract: In this systematic review, we aim to synthesize published evidence on the effects of exercise in improving postural stability among older adults with Alzheimer’s Disease (AD). A systematic electronic literature search was undertaken in Pedro, Cochrane, MEDLINE, ProQuest, Science direct and Clinical trial databases involving human participants published from year 2000–2022. This search was updated in June 2022. The studies chosen were based on predetermined criteria. Data relating to the contents and parameters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Interventions that target multiple fall risk factors have been more commonly tested in a clinical trial setting with mixed results [ 61 , 67 , 76 , 82 ]. For example, an intervention that included exercise and tailored home hazard removal among community-dwelling older adults with cognitive impairment [ 61 ] and an intervention that included medication review, vision correction, exercise, and home hazard modification in people with cognitive impairment did not reduce falls [ 82 ].…”
Section: Fall Prevention Interventions For Older Adults With Alzheime...mentioning
confidence: 99%
See 1 more Smart Citation
“…Interventions that target multiple fall risk factors have been more commonly tested in a clinical trial setting with mixed results [ 61 , 67 , 76 , 82 ]. For example, an intervention that included exercise and tailored home hazard removal among community-dwelling older adults with cognitive impairment [ 61 ] and an intervention that included medication review, vision correction, exercise, and home hazard modification in people with cognitive impairment did not reduce falls [ 82 ].…”
Section: Fall Prevention Interventions For Older Adults With Alzheime...mentioning
confidence: 99%
“…For example, an intervention that included exercise and tailored home hazard removal among community-dwelling older adults with cognitive impairment [ 61 ] and an intervention that included medication review, vision correction, exercise, and home hazard modification in people with cognitive impairment did not reduce falls [ 82 ]. However, a recent review of fall prevention interventions found that those targeting strength, balance, and cognition (executive function) can improve postural stability and may reduce the risk of falling among older adults with AD [ 67 ]; however, additional research is needed to examine the effectiveness of multicomponent fall prevention interventions for older adults with AD.…”
Section: Fall Prevention Interventions For Older Adults With Alzheime...mentioning
confidence: 99%
“…In order to enhance functional capacity and prevent falls in older adults (65 years and older), it is recommended to incorporate in the lifestyle a diverse multicomponent physical activity on three or more days a week that emphasizes functional balance and strength training at moderate or greater intensity [ 284 ]. A recent review suggests that combined muscle strength, balance and motor function training can improve postural stability in older adults with AD and reduce cases of falls [ 285 ]. However, this type of training does not seem to be different for elderly people without AD.…”
Section: Individual Approachesmentioning
confidence: 99%
“…Physical activity now forms a key part of many clinical recommendations for the management of dementia [ 3 , 4 ]. Physical activity interventions improve fitness, balance, and mobility [ 5 ], reduce feelings of distress, and may decrease fall risk [ 6 , 7 ]. Physical activity participation may also reduce cognitive decline among persons with dementia [ 8 , 9 ], though not all studies agree [ 10 ].…”
Section: Introductionmentioning
confidence: 99%